Manifestations of polyculturalism in Indonesia: A study of indigenous psychology. - Khasanah, Nurul; Mashuri, Muhammad Fath; Karmiyati, Diah (Universitas Muhammadiyah Surakarta, 2021)
Abstract. Polyculturalism is an ideology that emphasizes the interaction between certain cultures. Polyculturalism is considered to minimize prejudice and potential conflicts, while studies on polyculturalism in Indonesia are still limited. The purpose of this study is to find out the aspects of polyculturalism in Indonesia and what conditions make individuals open to establish relationships with other individualsso that it has the potential to become the nation's glue. This research uses indigenous psychology approach with mix method design. Subjects selected with the criteria of Indonesian Citizens (Citizens), aged 18 years and over, and have migrated more than 2 years (between cities / provinces in Indonesia). Dataanalysis was carried out in two ways, firstly a qualitative analysis that is making a categorization system through the bottom up indigenization model. Second, conduct quantitative analysis using descriptive analysis and chi-square test. The results of this study reveal aspects of cultural equality as national identityincluding, tolerance, citizenship, culture and race. While aspects that distinguish cultures in Indonesia consist of cultural, racial, geographical and religious rituals. Furthermore, aspects that make individuals establish inter-group relations include curiosity about other cultures, social relations, tolerance, geography, environment, openness, individual values, and emotional conditions. The psychological implications of these results also form part of the research in this study.Keywords: identity; indigenous pychology; polyculturalism